ONE GROUP TEST: LITERASI SEBAGAI UPAYA PENINGKATAN KEMAMPUAN SISWA DALAM MENGENALI BAHAN PAKAN TERNAK - Heri Yusmargana; Ita Prihantika (Wacana Publik, 2022)
One of the important roles of SMK is to produce specific human capital, rather than general human capital. However, SMK faces problems including: less varied learning methods; the learning delivered has not been integrated with literacy; the lack of HOTS (higher order thinking skill) based learning models in learning; and information and communication technology (ICT) has not been applied to the manufacture of learning media. With a quantitative approach, the research team conducted a one group pretest and posttest design experiment to intervene in the research object (29 students of class XI ATR 1), with literacy activities for 15 minutes. Literacy activities by identifying animal feed ingredients and their nutritional sources, show changes in the form of increasing object abilities by an average of 30.86 points. The gain normality test (N-Gain) showed that 68.97% experienced a moderate change or as many as 20 students, seven people experienced a high increase (27.59%) and only one person (3.45%) experienced a low increase. Thus it was concluded that this study is in line with previous studies which revealed that literacy can improve students' reading abilities and interest.